Heidegger's critique of the technology and the educational ecological imperative - Huttunen Rauno; Kakkori Leena (Routledge, Taylor & Francis Group, 2025)
It is clear that we have to do something in our time concerning global warming yet before we can actually change the world, we must first understand our world. According to Heidegger, technology itself is not good or bad, but the problem is, that technological thinking (calculative thinking) has become the only form of thinking. Heidegger saw that the essence of technology nowadays is enframing - Ge-stell, which means that everything in nature is 'standing-reserve' (Bestand). Enframing (as apparatus) is one way of uncovering, which for Heidegger meant truth. Truth can appear in many ways and the danger is that this truth of representational-calculative thinking becomes the only truth. We claim that the calculative way of thinking must be changed and we posit that Gelassenheit (slow thinking, releasement, letting-go) is the remedy. It does not mean some kind of mysticism or irrationality. The notion of Gelassenheit includes the idea of to let learn. We as teachers and educators have to learn how to think outside of the technological 'Ge-stell' and start thinking and acting in radically new ways. Like Arne Naes and Michael Zimmerman we connect the overcoming of technological 'Ge-stell' with so called deep ecology. We have to 'learn to think' and act within the deep ecology. We call for an educational ecological imperative. Every teacher and educationalist has to think what they can do (not as private person but as professionals) in order to prevent the coming eco-catastrophe.